William Wirt papers - Wirt, William, 1772-1834.
Correspondence, writings, reminiscences, clippings, and other papers pertaining primarily to the Wirt (Werth) family, a Southern slaveholding family. Topics include social life in Baltimore, Md., Richmond, Va., and Washington, D.C., Christian piety, and sickness and death in the Wirt family. Also includes material concerning the trial of Aaron Burr, legal work conducted by Wirt as U.S. district attorney, Richmond, Va., 1816, and as U.S. attorney general, 1817-1829, Wirt's 1832 presidential campaign on the Anti-Masonic ticket, the efforts of Wirt and his son-in-law, Louis Malesherbes Goldsborough, to settle German farmers near Monticello, Fla., Wirt's book titled, The Letters of the British Spy (1803), and reactions to Wirt's biography of Patrick Henry.
In addition to family members, correspondents include John Quincy Adams, Nicholas Biddle, William H. Cabell, John C. Calhoun, Dabney Carr, Robert Gamble, Peachy R. Gilmer, Thomas Jefferson, James Madison, James Monroe, Abner Phelps, Richard Rush, James Wallace, James Webster, and Lewis Williams.
Microfilm edition available
Microfilm produced from originals in Manuscript Division.
U.S. attorney general, lawyer, politician, and biographer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Biddle, Nicholas, -- 1786-1844 -- Correspondence; Burr, Aaron, -- 1756-1836 -- Trials, litigation, etc; Cabell, William H., -- 1772-1853 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Carr, Dabney, -- 1773-1837 -- Correspondence; Gamble, Robert, -- 1754-1810 -- Correspondence; Gilmer, Peachy R. -- 1779-1836 -- Correspondence; Goldsborough, Louis Malesherbes, -- 1805-1877.; Henry, Patrick, -- 1736-1799.; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Phelps, Abner, -- 1779-1873 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Wallace, James -- Correspondence; Webster, James -- Correspondence; Williams, Lewis, -- 1786-1842 -- Correspondence; Werth family; Werth family -- Correspondence; Antimasonic Party; Attorneys general -- United States; Death; Diseases; Elections -- United States -- 1832.; Germans -- Florida; Law -- United States; Law -- Virginia -- Richmond; Piety; Public prosecutors -- Virginia -- Richmond; Slaveholders; Slavery; Baltimore (Md.) -- Social life and customs; Germany -- Emigration and immigration; Maryland -- Social life and customs; Monticello (Fla.) -- History; Richmond (Va.) -- Social life and customs; Southern States -- Social life and customs; Virginia -- Social life and customs; Washington (D.C.) -- Social life and customs; Biographers